Proteins, Nature's Versatile Devices - Aboderin, A. (Obafemi Awolowo University Press, 2013)
It is our intentions in this lecture to explore some of the unities that characterise life from the intellectual niche of the protein molecule. To the extent that it can be demonstrated that the choice is not a parochial one, but one that belongs, if not at the centre, close to the centre of the phenomenon of life, to that extent will the intention of this discourse have been fulfilled. As is usual in this type of setting however it is fit and proper for me to seek the understanding of both the initiates and the laity, obviously for very different but understandable reasons. Proteins, as nature's versatile devices, function within comparatively macroscopic entities known as cells. As all students of biology and the history of biology are aware, the cell is the basic unit of biological life. As everyone again is aware there are different kinds of cells, In multicellular organisms such as the present lecture, there are brain cells, liver cells, kidney cells, all of which, within the proper observational grid, not only look different but also have different properties and functions.